2016
DOI: 10.3390/molecules21121697
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of Alkyne Reactivity in Copper-Catalyzed Azide-Alkyne Cycloadditions

Abstract: This work represents our initial effort in identifying azide/alkyne pairs for optimal reactivity in copper-catalyzed azide-alkyne cycloaddition (CuAAC) reactions. In previous works, we have identified chelating azides, in particular 2-picolyl azide, as "privileged" azide substrates with high CuAAC reactivity. In the current work, two types of alkynes are shown to undergo rapid CuAAC reactions under both copper(II)-(via an induction period) and copper(I)-catalyzed conditions. The first type of the alkynes bears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…Deuterium kinetic isotope effect (KIE) experiments of the alkyne C À Hw ere informative.Z hu et al reported ap rimary KIE of 2.3 when using an aryl alkyne (such as 5) and am arked increase in the initiation time associated with oxidative homocoupling. [8] In agreement with these data, we observed primary KIEs (e.g.,KIE for 2 = 2.66) and asignificant increase in initiation time (see SI). In contrast aK IE of only 1.17 was observed for 1 (Figure 2a), indicating that Cuacetylide formation was not rate limiting.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…Deuterium kinetic isotope effect (KIE) experiments of the alkyne C À Hw ere informative.Z hu et al reported ap rimary KIE of 2.3 when using an aryl alkyne (such as 5) and am arked increase in the initiation time associated with oxidative homocoupling. [8] In agreement with these data, we observed primary KIEs (e.g.,KIE for 2 = 2.66) and asignificant increase in initiation time (see SI). In contrast aK IE of only 1.17 was observed for 1 (Figure 2a), indicating that Cuacetylide formation was not rate limiting.…”
supporting
confidence: 87%
“…[3,5] 3) Fokin et al have developed chemoselective CuAACr eactions of 1-iodoalkynes that, due to their mechanistically distinct operation, have allowed for highly chemoselective reactions versus conventional terminal alkynes. [6] Based on work by Finn and Fokin, [7] and Zhu, [8] acetylide formation is the rate-determining step (RDS) of the CuAAC reaction (Scheme 1). [9] Chemoselective discrimination of alkynes is therefore possible by exploiting differences in their respective rates of acetylide formation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Highly electron‐deficient alkynes such as ethynyl ketones failed to result in alkynyltriazole formations for a different reason. These alkynes (1) are not as prone to oxidation but highly reactive in the cycloaddition with an azide, and (2) tend to undergo the redox neutral Michael addition with MeOH in the presence of a base. Therefore, protiotriazole, bistriazole, and the solvent adduct to the alkyne were common products from these reactions (Scheme S4).…”
Section: Resultsmentioning
confidence: 99%